Recent developments in X-UV optics and X-UV diagnostics - Levecq, X., author; Valentin, C., author; Troussel, P., author; Smith, R. F., author; Rocca, Jorge J., author; Rémond, C., author; Ravet, M. F., author; Naulleau, P. P., author; Morlend, A. S., author; Mercère, P., author; Marmoret, R., author; Lewis, C. L. S., author; et al. (Colorado State University. Libraries, 2004)
Metrology of XUV beams (X-ray lasers, high-harmonic generation and VUV free-electron lasers) is of crucial importance for the development of applications. We have thus developed several new optical systems enabling us to measure the optical properties of XUV beams. By use of a Michelson interferometer working as a Fourier-transform spectrometer, the line shapes of different X-ray lasers have been measured with a very high accuracy (Δλ/λ ∼ 10−6). Achievement of the first XUV wavefront sensor has enabled us to measure the beam quality of laser-pumped as well as discharge-pumped X-ray lasers. A capillary discharge X-ray laser has demonstrated a very good wavefront allowing us to achieve an intensity as high as 3 × 1014 W cm−2 by focusing with a ƒ = 5 cm mirror. The sensor accuracy has been measured using a calibrated spherical wave generated by diffraction. The accuracy has been estimated to be as good as λ/120 at 13 nm. Commercial developments are underway. At Laboratoire d'Optique Appliquée, we are setting up a new beamline based on high-harmonic generation in order to start the femtosecond, coherent XUV optic.